New energy simulation software improves features of old tools and offers more flexibility. - Solomon, Nancy B. (Architectural Record, 2001)
Reports on the development of EnergyPlus simulation software by the Department of Energy in the United States. Features of the software; Reliance of the program on an integrated simulation process; Advantage of digital architecture.